Task-Based Activities to Improve Oral Communication Skills in Adult Learners - Detken, María Belén; Ramirez-Avila, Maria Rossana; Chancay, Carlos Humberto (Journal of Foreign Language Teaching and Learning, 2000)
In-service teachers in an online course had problems interacting in English. They experienced negative feelings when they had to perform orally. Thus, this action research study with qualitative and quantitative data analysis aimed to apply task-based activities to improve spoken interaction. The sample was twenty-five in-service teachers. Their level of English was A2 according to the Common European Framework of Reference. Their ages ranged between thirty and fifty. The participants were teachers from different public schools on the Coast of Ecuador. Pre and post-tests were applied to compare participants' performance from the beginning and after the intervention. Findings disclosed that the mean raised from 17.72 to 19.12, and p<0.000 is interpreted as the results are statistically significant and task-based activities improve students’ speaking performance. In-service teachers showed that as their confidence increased in their oral performance, their frustration and anxiety were reduced. Lastly, participants commented that they replicated some task-based activities in their classes. The implications of this study involve other English teachers, EFL researchers, and students who want to apply the same strategy in their teaching and learning process.